Peran Tokoh Agama Dalam Penyusunan Peraturan di Kelurahan Pulo Brayan Darat II Kecamatan Medan Timur Menurut Perspektif Fiqh Siyasah. - Indah Nurhidayah; Nana Rafiana; Rani Najmatun Hikmah; Winda Syaharani; Esty Dewi Anggraini (Tabayyun : Journal Of Islamic Studies, 2023)
This research aims to describe the role of religious figures in the process of drafting regulations at the sub-district level, especially in Pulo Brayan Darat II Subdistrict, East Medan District. This research uses descriptive research with a qualitative approach with field research. The research location was carried out at the Pulo Brayan Darat II Subdistrict Office and the Al-Ma'ruf Sidorukun Mosque. The results of this research show that in drafting regulations in Pulo Brayan Darat II Subdistrict, religious figures have a quite significant role. This is because the drafting of regulations in the area was carried out through open and deliberative discussions involving community leaders and other community representatives, such as mosque youth and youth organizations. Meanwhile, the role of religious figures in drafting regulations is in accordance with the perspective of fiqh siyasah, because according to fiqh siyasah, religious figures are good role models for society, provide solutions to society's problems, implement amar ma'ruf and nahi munkar, and form a society that is lawful. good and moral role models to create a safe, peaceful and prosperous community life.